Empowering local communities in Ngrambe Village through service learning and entrepreneurship - Deatri Arumsari Agung; Gesti Memarista; Eric Sulindra; Aldo Hardi Sancoko; Rianmahardhika Sahid Budiharseno (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2026)
The CED Program of Universitas Katolik Widya Mandala Surabaya aimed to empower small businesses in Ngrambe through service-learning and social entrepreneurship to address local socio-economic challenges. The program integrates academic knowledge with practical experience to promote sustainable development, community collaboration, and rural economic resilience. Using a structured methodology, participants improved their business operations by focusing on social media management and product development. The program supported 13 small businesses with 54 facilitators (9 lecturers and 36 students) from 4 institutions, which included international participants from 6 different countries. A preliminary survey identified the needs of local businesses, followed by planning and the implementation of service-learning projects. The program's impact was evaluated through targeted questionnaires. Small businesses in Ngrambe, Ngawi, benefited significantly from enhanced product packaging, creative digital marketing strategies, and business training, resulting in increased consumer interest and expanded online market reach. Meanwhile, participating students gained hands-on experience in business management and social entrepreneurship, while developing professional skills, cross-cultural collaboration, and social awareness. This collaborative initiative strengthened local businesses, fostered sustainable growth, and positively influenced the local economy and community dynamics.